Determinants of the utilization of public pharmacies: Results of a population survey in the federal state of Bavaria in Germany - Faß, Eric; Thiesen, Josephine; Weinhold, Ines; Claus, Franziska (Das Gesundheitswesen, 2025)
Public pharmacies are important for healthcare in Germany, despite decrease in their number over several years. Considering demographic aging and an expected increase in demand for pharmacy-specific services, adequate organization of pharmacy care services for specific target groups and regions is, therefore, highly relevant. For this, knowledge of utilization patterns and their determinants is crucial. This study aims to identify the determinants of visiting public pharmacies, while focusing on the relation of age and morbidity, by analyzing mediation effects. Additionally, specific target groups of public pharmacies will be identified.As data basis, a telephone survey was carried out in the federal state of Bavaria in Germany. The sample consists of 436 participants. To identify determinants of utilization, weighted generalized linear models were carried out. Next, causal mediation analysis was applied to analyze how much the association between age and visiting a public pharmacy may be explained by morbidity. Additionally, population groups with the highest predicted probability of a pharmacy visit as well as the most predicted pharmacy visits were identified.Females (AME=0.072), older people (AME=0.086) and those who have at least one disease (AME=0.147) were found to have a higher, people with higher educational attainment (AME=−0.076) a lower probability of having visited a public pharmacy. Causal mediation analysis revealed a mediation effect of morbidity in the relation between age and public pharmacy visit (about 14%). Additionally, older women living in rural regions were found to have the highest predicted probability of having visited a public pharmacy.The results of this study highlight the need for further research regarding the determinants of pharmacy care utilization, especially focusing on their interplay. This is crucial for organizing future target group-specific pharmacy services when facing an increased demand with a simultaneous decrease in supply.
Keywords: Leistungsinanspruchnahme; öffentliche Apotheken; Mediationsanalyse